2017
DOI: 10.1097/aog.0000000000002325
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuing Oxytocin Infusion in the Active Phase of Labor

Abstract: In singleton gestations with cephalic presentation at term undergoing induction, discontinuation of oxytocin infusion after the active phase of labor at approximately 5 cm is reached reduces the risk of cesarean delivery and of uterine tachysystole compared with continuous oxytocin infusion. Given this evidence, discontinuation of oxytocin infusion once the active stage of labor is established in women being induced should be considered as an alternative management plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 23 publications
0
32
2
1
Order By: Relevance
“…A previous meta-analysis of nine randomized controlled trials compared continuation and discontinuation of oxytocin after the active phase of labor and its effect on labor induction and labor augmentation [7][8][9][10][11][12][13][14][15]24]. In that meta-analysis, oxytocin discontinuation after the active phase of labor signi cantly lowered the cesarean delivery rate (9.3% vs 14.7%) and uterine tachysystole rate (6.2% vs 13.1%) compared with oxytocin continuation until delivery [24]. When labor enters the active phase, further oxytocin administration does not seem to have any bene t except for shortening the labor length.…”
Section: Discussionmentioning
confidence: 99%
“…A previous meta-analysis of nine randomized controlled trials compared continuation and discontinuation of oxytocin after the active phase of labor and its effect on labor induction and labor augmentation [7][8][9][10][11][12][13][14][15]24]. In that meta-analysis, oxytocin discontinuation after the active phase of labor signi cantly lowered the cesarean delivery rate (9.3% vs 14.7%) and uterine tachysystole rate (6.2% vs 13.1%) compared with oxytocin continuation until delivery [24]. When labor enters the active phase, further oxytocin administration does not seem to have any bene t except for shortening the labor length.…”
Section: Discussionmentioning
confidence: 99%
“…non-progression of the cervical dilation during the latent phase [9][10][11]. One assumption is that, once women requiring oxytocin during the latent phase enter the active phase, natural oxytocin takes over from synthetic oxytocin [12]. Thus, in the active phase, oxytocin could be discontinued, reducing exposure duration and therefore reducing the risk of complications, in particular neonatal complications such as hypoxia, without compromising the chances of vaginal delivery.…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…All these studies but one [15] were randomized, none used blinding, and the largest sample size was of 342 women (168 vs 174) [16]. Most of these studies, as well as the metanalysis [12] including them, showed a longer length of active phase of labor in the discontinuation of oxytocin group (in the metanalysis the mean difference was 27.65 min, 95%CI 3.94-51.36). None of these previous published trials, nor the meta-analysis combining these trials [12] showed an increase in the cesarean delivery rate in the discontinuous oxytocin group, on the contrary, the meta-analysis showed a significant decrease in the cesarean delivery rate in the discontinuous oxytocin group (9.3% compared with 14.7%; RR 0.64, 95%CI 0.48-0.87).…”
Section: Previous Published Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cochrane veri tabanında yapılan bir derlemede; erken dönemde oksitosin uygulamasının sezaryen doğum oranlarında orta derecede bir azalmaya neden olduğu ve doğum süresini kısalttığı belirtilmiştir (26). Ancak doğumun aktif fazından sonra oksitosin uygulamasına devam edilen ve edilmeyen grupların karşılaştırıldığı, dokuz araştırmanın değerlendirildiği bir meta-analiz çalışmasında; oksitosin infüzyonuna devam edilen grupta sezaryen ve uterin taşisistoli riskinin arttığı belirtilmiştir (43). Yine bazı çalışmalarda oksitosin kullanımının maternal ve neonatal yan etkilere neden olduğu belirtilmiştir.…”
Section: Forseps Ve Vakumunclassified